PENINGKATAN LITERASI KEUANGAN MENGGUNAKAN PENDEKATAN HEURISTIK (Studi Kasus pada Pedagang Tradisional yang Dikelola oleh PD Pasar Bermartabat): PENINGKATAN LITERASI KEUANGAN MENGGUNAKAN PENDEKATAN HEURISTIK (Studi Kasus pada Pedagang Tradisional yang Dikelola oleh PD Pasar Bermartabat) - khairunnisa runny Effendi; Leny Suzan; Kurnia . (Universitas Widyatama, 2020)
Community service activities can be used as a way to increase financial literacy in traditional traders managed by PD Pasar Bermartabat. The results of the 2019 National Financial Literacy Survey show the financial literacy index figure of 38.03%. This figure shows that most Indonesians are not included in the well literate category. In practice, traditional market traders are familiar with loan sharks in their daily business activities. One of the limitations of this community service activity is the limited time because the target community is an active UMKM actor with a long working time. To overcome this limitation, it is necessary to have an appropriate learning model in improving financial literacy, namely the heuristic learning model. This financial literacy research data was measured using a questionnaire from Carpena's financial literacy dimensions. To find out the differences in financial literacy before and after the implementation of the heuristic learning model, the paired t-test was used different test with a significance level of 0.05. The number of respondents was 30 market representatives managed by PD Pasar Bermartabat. The results of this study indicate that the heuristic learning model can improve the financial literacy of traditional market traders managed by PD Pasar Bermartabat.